The cholinergic system in cyclophosphamide induced-Chagas dilated myocardiopathy in Trypanosoma cruzi infected rats: an electrocardiographic study. - Labrador-Hernández, Marialeycnan; Suárez-Graterol, Oscar; Romero-Contreras, Urimare; Rumenoff, Lila; Rodríguez-Bonfante, Claudina; Bonfante-Cabarcas, Rafael (Investigación Clínica, 2009)
Chronic Chagasic Cardiomyopathy (CCC) has been re lated to the cholinergic sys tem by the neurogenic and autoimmune theories. The neurogenic the ory ex plains cardiomyopathy as a re sult of post-gan gli onic para - sympathetic denervation. Cyclophosphamide (CP) facilitates the development of autoim mune disease because of a selective depletion of suppressor T cells. In this study we char ac ter ized the phenylephrine-in duced vasovagal re flex us ing se lec tive cholinergic drugs, in two rat mod els: Trypanosoma cruzi (TC) in - fected an i mals and CCC CP-treated rat model. To achieve this goal, 3 week old-90 Sprague Dawley rats were di vided into four groups: Con trol (C), CP, TC and TCCP; TC and TCCP were in oc u lated with 1000 trypomastigotes/g; CP and TCCP were treated with CP 20 mg/Kg twice a week for five times. Af ter 6 months, the stud ied an i mals un der went electrocardiographic (EKG), ra dio - graphic (Rx) and histopathological (HP) assesments. The vagal in teg rity was eval u ated by ap pli ca tion of phenylephrine (PE) plus tacrine, while the muscarinic cholinergic func tion was eval u ated us ing se lec tive M1, M2, M3 and M4 muscarinic an tag o nists. Our data show show that TCCP rats dis played the high est fre quency of EKG, Rx and HP dis tur bances. TC and TCCP rats ex hib - ited a de creased re sponse to: 1) phenyl ephrine-in duced vagal baroreflex brady cardia; 2) methoctramine-, 4-DAMP- and tropicamide-in duced tachy car - dia; 3) methoctramine-in duced QRS short en ing, and 4) tropicamide-in duced QT prolongation. In conclusion, CP fa cil i tates the de vel op ment of CCC in Trypanosoma cruzi in fected rats, by pro mot ing para sym pa thetic dis tur bances that ap pear as con se quence of al ter ations on the muscarinic re cep tor dis tri - bu tion at dif fer ent neu ral integration levels.